Effects of acoustic power and pH on pectin‐enriched extracts obtained from citrus by‐products. Modelling of the extraction process - Umaña, Mónica M; Dalmau, María E; Eim, Valeria S; Femenia, Antoni; Rosselló, Carmen (Journal of the science of food and agriculture, 2019)
BACKGROUND The ultrasound‐assisted extraction of pectic polysaccharides from orange by‐products was investigated. Kinetics of mechanical agitation (0.2 × g) and acoustic (US1: 542 W L−1 and US2: 794 W L−1) extractions, were obtained and modelled at different pH values (1.5 and 2.0). All extractions were carried out at 25 °C, using citric acid as the extraction solvent. RESULTS Higher pectic polysaccharides extraction yields were obtained with ultrasonic assistance, in comparison with the results obtained using mechanical agitation. Moreover, yield increases were significantly higher using the more acidic pH. Thus, at pH 1.5, pectin yield increased from ∼19%, obtained with agitation, to ∼47%, applying ultrasound; whereas, at pH 2.0, this increase was from ∼10%, with agitation, to ∼18%, applying ultrasound. A considerable decrease of the galacturonic acid proportion was observed on the extracts when ultrasound were applied for 60 min under pH 2.0. High methoxyl pectins were extracted at pH 1.5 whereas at pH 2.0, pectins exhibited a low methylation degree. Curves of acoustic and mechanical agitation extractions were properly represented by a second‐order rate model (average mean relative error ≤ 7.4%). The extraction rate constant, initial extraction rate and maximum yield were determined for all experimental conditions. CONCLUSION Overall, the results clearly indicated that the effect of ultrasound was highly dependent on the pH. Therefore, adequate acidic conditions must be applied in order to improve the efficiency of ultrasound on the pectin extraction process. © 2019 Society of Chemical Industry